Pyomyoma in a Young Nulliparous Woman - A Case Report - Rauf, Manal (International Journal of Pathology, 2019)
Pyomyoma (Acute Suppurative Leiomyoma) is a very rare complication of uterine leiomyoma and is associated with high mortality and morbidity if not promptly treated. We report a case of pyomyoma in young nulliparous woman due to ascending infection. Our patient presented with continuous abdominal pain and per vaginal bleeding. She had no previous workup up. Myomectomy was performed that revealed pyomyoma. Pyomyoma should be suspected in a patient with leiomyoma and unexplained abdominal pain and fever